Activity Limitations, Participation, and Quality of Life in American Indians with and without Diabetes. Issue 1 (2nd January 2016) - Poole, Janet L.; Gashytewa, Carrie; Sullivan, Anne T.
ABSTRACT: The objective of this study was to examine activity limitations, participation, and quality of life (QOL) in American Indians with and without diabetes. It was a cross-sectional study that included 43 participants with diabetes and 31 healthy controls. Participants received evaluations of QOL, activity and participation limitations and factors such as pain, joint motion, hand function, and depression. There were no significant differences between the two groups for past, present, or future global QOL. However, there were significant differences between the two groups for the activity and participation measures and all measures of body structure/function except for left hand strength and depression. Current health and pain, and activity limitation correlated with QOL in both groups. Joint motion and participation correlated with QOL in the group with diabetes. American Indians with diabetes had more impairments in body structure and function and limitations in activities and participation compared to American Indians without diabetes.